Using final black hole spins and masses to infer the formation history of the observed population of gravitational wave sources - Arca Sedda, Manuel; Benacquista, Matthew J. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. In this paper, we propose a novel technique to constrain the progenitor binary black hole (BBH) formation history using the remnant masses and spins